Impact of prior anterior cruciate ligament, hamstring or groin injury on lower limb strength and jump kinetics in elite female footballers. (November 2021) - Collings, Tyler J.; Diamond, Laura E.; Barrett, Rod S.; Timmins, Ryan G.; Hickey, Jack T.; du Moulin, William S.; Gonçalves, Basílio A.M.; Cooper, Christopher; Bourne, Matthew N.
Abstract: Objective: To compare lower limb strength and countermovement jump (CMJ) kinetics between elite female footballers with and without a history of anterior cruciate ligament reconstruction (ACLR), hamstring strain, or hip/groin injury. Design: Cross-sectional. Setting: Field-based. Participants: 369 elite female Australian football, soccer and rugby league players aged 15–35. Main outcome measures: Isometric hip adductor and abductor strength, eccentric knee flexor strength, and CMJ vertical ground reaction forces, including between-leg asymmetry. Players reported their lifetime history of ACLR, and whether they had sustained a hamstring strain, or hip/groin injury in the previous 12-months. Result s : Players with a unilateral history of ACLR (n = 24) had significant between-leg asymmetry in eccentric knee flexor strength (mean = −6.3%, 95%CI = −8.7 to −3.9%, P < .001), isometric hip abductor strength (mean = −2.5%, 95%CI = −4.3 to −0.7%, P = .008), and CMJ peak landing force (mean = −5.5%, 95%CI = −10.9 to −0.1%, P = .046). Together, between-leg asymmetry in eccentric knee flexor strength, isometric hip abductor strength, and CMJ peak landing force distinguished between players with and without prior ACLR with 93% accuracy. Conclusion: Elite female footballers with a history of ACLR, but not hamstring or hip/groin injury, exhibit persistent between-leg asymmetries in lower limb strength and jump kinetics following a return to sport. Highlights: Elite female footballers with prior ACLR display chronic between-leg asymmetries in knee flexor strength, hip abductor strength, and jump-landing force. Lower limb strength and jump kinetics are not impaired after hamstring or hip/groin injury. These data may have implications for ACLR rehabilitation and return to sport criteria.